If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8h + -26 = 37 + 13h Reorder the terms: -26 + -8h = 37 + 13h Solving -26 + -8h = 37 + 13h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-13h' to each side of the equation. -26 + -8h + -13h = 37 + 13h + -13h Combine like terms: -8h + -13h = -21h -26 + -21h = 37 + 13h + -13h Combine like terms: 13h + -13h = 0 -26 + -21h = 37 + 0 -26 + -21h = 37 Add '26' to each side of the equation. -26 + 26 + -21h = 37 + 26 Combine like terms: -26 + 26 = 0 0 + -21h = 37 + 26 -21h = 37 + 26 Combine like terms: 37 + 26 = 63 -21h = 63 Divide each side by '-21'. h = -3 Simplifying h = -3
| 4-n=-11 | | 81x^4-16=0 | | y=x+7 | | 2-(17-5x)=9x-(x+7) | | 2(x-3)=-1 | | 8x+y=18 | | n-6m=8 | | y=25-4x | | 2(2q+4)-20=12 | | 25c+17=-5c+143 | | 4x+5y=-10 | | 18x-16=19x-15 | | (-0.8)(17)(-0.02)= | | 8+(-5)= | | 8c+6j=5p | | 7a+2(13-a)=196 | | 7n+9=44-6n | | 4y+3=-7 | | bc+3g=2k | | 0=4x^2-12x+9 | | 25x+5=10 | | 8m-2(5-m)=41 | | 7x-6=6x-5 | | 0.25x+10=12 | | 0.027x+2=0.035x | | m+3n=1 | | 6x+8=4x+12 | | 3+3a=2(7a+7) | | 3(b+3)+9=45 | | x+21=-x+87 | | 10-y=3 | | 10x-2(x+5)=25 |